Violation of Grice Maxims to Create Humor: An Analysis of Sitcom “khaber daar” - Fatima, Shehnaz; Kayani, Taimur; Jalali, Aroosa A (Pakistan Journal of Humanities and Social Sciences, 2023)
Pragmatics is a branch of linguistics that studies how context affects meaning and how human language can be perceived differently. All of our communications rely on the compatibility of interpreters and interpreted. Communication issues can be resolved by improving speaker and listener interaction. Therefore, by working together, the speaker and the listener can comprehend two meanings in a single phrase. The more comprehensive intercultural aspect of language is shown through pragmatics. Grice (1975) introduced the idea of the Cooperative Maxims Principles, which aids in conversation analysis. The current study examines instances of Grice conversational maxim violations in the well-known sitcom "Khaberdaar," which is broadcasted on Express news. It is a comedic television program in Urdu and Panjabi. The anchor person introduces the subject or an issue in the first part. The actor-comedian introduces themselves as a parody guest, puts on a little skit, or makes fun of prominent people by dressing up as athletes, politicians, or actors. The researcher discovers that humor arises anytime the speakers violate any one of four maxims. In this study, it is also examined how verbal humor in the sitcom "Khaberdaar" is produced via maxim violations. Therefore, this sitcom also has a message in addition to its humor. The researcher concludes after studying four episodes of the sitcom "Khaberdaar" that the maxim of relevance is the one that is most frequently broken, followed by the maxims of quality, manners, and quantity. The researcher discovers that the speaker effectively communicates his point while breaking the conversational rules. By appropriately violating Grice maxims that make listeners laugh as well as cry, social issues can be subtly brought to the listeners' attention.